Natural Language Procession - NLP 2000 : second international conference Patras, Greece, June 2-4, 2000 proceedings - Christodoulakis, Dimitris N. (Germany : Springer, 2000)
This volume contains the papers prepared for the 2nd International Conference on Natural Language Processing, held 2-4 June in Patras, Greece.
Parsing Asymmetries / A.-M. Di Sciullo -- Universal Segmentation of Text with the Sumo Formalism / J. Quint -- Functional Decomposition and Lazy Word-Parsing in Modern Greek / E. Papakitsos, M. Gregoriadou and A. Ralli -- Recognition and Acquisition of Compound Names from Corpora / G. Nenadic and I. Spasic -- Use of a Morphosyntactic Lexicon as the Basis of the Implementation of the Greek WordNet / A. Ntoulas, S. Stamou and I. Tsakou / [and others] -- On Verb Selectional Restrictions: Advantages and Limitations / F. Gayral, N. Pernelle and P. Saint-Dizier -- Some Principles for Implementing Underspecification in NLP Systems / A. Mari and P. Saint-Dizier -- HYPERTAGS: Beyond POS Tagging / A. Kinyon -- A Theory of Stochastic Grammars / C. Samuelsson -- Monte-Carlo Sampling for NP-Hard Maximization Problems in the Framework of Weighted Parsing / J.-C. Chapplier and M. Rajman -- Prepocessing for Unification Parsing of Spoken Language / M.-J. Nederhof -- A Semantic Based Approach for Spontaneous Spoken Dialogue Understanding / M.Z. Kurdi -- A Practical Chunker for Unrestricted Text / E. Stamatatos, N. Fakotakis and G. Kokkinakis -- A Distributed Approach for a Robust and Evolving NLP System / J. Balsa and G. Lopes -- An Incremental Discourse Parser Architecture / D. Cristea -- A Spatio-Temporal Model for the Representation of Situations Described in Narrative Texts / S. Gerard and J.P. Sansonnet -- Enhancing Preference-Based Anaphora Resolution with Genetic Algorithms / C. Orasan, R. Evans and R. Mitkov -- Anaphora Resolution through Dialogue Adjacency Pairs and Topics / M. Palomar and P. Martinez-Barco -- Semantic Knowledge-Driven Method to Solve Pronominal Anaphora in Spanish Texts / M. Saiz-Noeda and M. Palomar -- Processing of Spanish Definite Descriptions with the Same Head / R. Murioz and M. Palomar -- Constraints, Linguistic Theories and Natural Language Processing / P. Blache -- A Comparison of Rule-Based and Machine Learning Methods for Identifying Non-nominal It / R. Evans -- Constitution and Exploitation of Annotation System of Electronic Corpora: Toward Automatic Generation of Understandable Pronouns in French Language / C. Clouzot, G. Antoniadis and A. Tutin -- Generation of Spanish Zero-Pronouns into English / J. Peral and A. Ferrandez -- Combining Different Translation Sources / U. Kussner and D. Tidhar -- Parsing and Collocations / E. Wehrli -- Contextual Reasoning in Speech-to-Speech Translation / S. Koch, U. Kussner and M. Stede / [and others] -- Improving the Accuracy of Speech Recognition Systems for Professional Translators / Y. Ludovik and R. Zacharaski -- Generic Parsing and Hybrid Transfer in Automatic Translation / C. Laenzlinger, S. L'haire and J. Mengon -- Two Applications for a Non-context French Generator / L. Balicco, S. Ben-Ali and C. Ponton / [and others] -- From Language to Motion, and Back: Generating and Using Route Descriptions / G. Ligozat -- Corpus-Based Methodology in the Study and Design of Systems with Emulated Linguistic Competence / Z. Vetulani and J. Marciniak -- Dialogues for Embodied Agents in Virtual Environments / R. op den Akker and A. Nijholt -- Concordancing Revised or How to Aid the Recognition of New Senses in Very Large Corpora / D. Kokkinakis -- Learning Rules for Large-Vocabulary Word Sense Disambiguation: A Comparison of Various Classifiers / G. Paliouras, V. Karkaletsis and I. Androutsopoulos / [and others] -- Greek Verb Semantic Processing for Stock Market Text Mining / J. Kontos, I. Malagardi and C. Alexandris / [and others] Extracting Semi-structural Data -- Lessons Learnt / U. Kruschwitz, A. de Roeck and P. Scott / [et al.] -- A Term-Based Methodology for Template Creation in Information Extraction / K. Zervanou and J. McNaught -- A System for Recognition of Named Entities in Greek / S. Boutsis, I. Demiros and V. Giouli / [et al.].
Includes bibliographical references and index.
Keywords: NATURAL LANGUAGE PROCESSING (COMPUTER SCIENCE)